Strategi Program Sekolah Orang Tua Hebat dalam Menumbuhkan Pola Asuh Positif dan Literasi Budaya-Kewargaan Anak Usia Dini - Atik Yuliana; Ahmad Samawi; Sri Wahyuni (Efektor, 2025)
This study aims to examine the implementation strategy of the Great Parents Program in fostering positive parenting patterns and its contribution to the cultural literacy of early childhood at the Kasih Bunda Playgroup, Sambirejo Village, Madiun Regency. The study employs a qualitative descriptive approach with a case study design, involving eight program participants, facilitators, institution managers, and students as research subjects. Data was collected through in-depth interviews, participatory observation, and documentation, then analyzed using the interactive model by Miles, Huberman, and Saldana, which includes data condensation, data presentation, and drawing conclusions. The research findings indicate that the program equips parents with effective communication skills, consistent discipline practices, and appreciation for children, which encourages a shift toward more democratic and supportive parenting styles. The program also proved to instill cultural and civic values through the introduction of national symbols, folk tales, traditional games, and the practice of mutual cooperation, which were internalized in family activities. The research findings confirm that parenting programs can serve as a strategic tool in integrating positive parenting with cultural and civic literacy, while also strengthening the character and identity of young children.